Synthesis of 3-keto-quinolines from enaminones, anilines and DMSO: Transition metal free one pot cascade. Issue 30 (26th July 2019) - Wakade, Sandip Balasaheb; Tiwari, Dipak Kumar; Phanindrudu, Mandalaparthi; Pushpendra; Tiwari, Dharmendra Kumar
Abstract: An efficient and transition metal-free approach for the synthesis of functionalized 3-ketoquinolines from readily available anilines, enaminones and DMSO in the presence of K2 S2 O8 has been conducted. This one pot tandem reaction proceeds through [3+2+1] cycloaddition reaction involving DMSO, enaminones and amines. In this environmental benign approach, DMSO acts as both a one carbon source and the solvent. A broad range of variously substituted amines and enaminones are successfully employed in this one pot tandem process to access a broad range of substituted 3-ketoquinolines. Graphical abstract: Image 1